Pengaruh Jenis Zat Pewarna Terhadap Ketampakan Mikoriza Arbuskular Pada Akar Muda Thaumatophyllum Bipinnatifidum - Avilia, Alma; Salsabila, Nuriana; Febrianty, Rafiony Eka; Aisy, Rihadatul; Frandista, Saniyyah Cinta; Khastini, Rida Oktorida (Biosel Biology Science and Education, 2024)
Arbuscular mycorrhizae (MA) are a group of soil fungi that are widespread in terrestrial ecosystems and play an important role in influencing plant growth and ecosystem processes. Mycorrhizae are plants that colonize the cortex tissue of plant roots, occurring from a symbiotic association between fungi and plants that occurs during the active growth and development of plants, generally found in association with the roots of plants such as Thaumatophyllum bipinnatifidum. The root coloring carried out in this observation used four types of dye, namely methylene blue, blue food dye (koepoe-koepoe), blue textile dye (wantex) and blue printer ink. This observation aims to determine the effect of the type of dye on the visibility of arbuscular mycorrhiza on the roots of the Thaumatophyllum bipinnatifidum plant. Of the four dyes used, textile dyes are more effective in coloring arbuscular mycorrhiza roots, because the color can bind to the mycorrhiza, so that the mycorrhiza can be easily distinguished. This is because textile dyes have good fastness compared to other dyes. Keywords: Arbuscular Mycorrhiza (AM), Root Coloring, Textile Dyes